THE CORRELATION BETWEEN AGE AND PARITY WITH WEIGHT GAIN DUE TO 3-MONTH INJECTABLE CONTRACEPTIVE USE AT BPM SITI AISAH CLINIC IN PENER VILLAGE, PANGKAH DISTRIC, TEGAL REGENCY - Diah Atmarina Yuliani; Alfi, Alfi Rizki Atun (Jurnal Kesehatan Panrita Husada, 2024)
ABSTRACT Background: Women using DMPA contraception, or 3-month injectable contraceptive, on average experience a weight gain of 11 pounds or 5.5 kg and an increase in body fat of 3.4% over a period of 3 years of use. The results of the 2022 Riskesdas (Basic Health Research) show a prevalence of overweight and obesity in Jawa Tengah Province of 20%. Objective: To determine whether there is a relationship between age and parity with weight gain due to the use of 3-month injectable contraceptive at BPM Siti Aisah Clinic in Pener Village, Pangkah Subdistrict, Tegal Regency. Method: This study is an observational analytical research with a cross-sectional approach. The population of this study consists of all contraceptive users at the Independent Midwife Practice Siti Aisah, totaling 78 respondents. Data analysis was conducted using univariate and bivariate analyses. Research Findings: The statistical test results for the age and parity variables yielded a p-value of 0.000. Conclusion: In conclusion, there is a relationship between age and parity with the occurrence of weight gain due to 3-month injectable contraceptive use at BPM Siti Aisah Clinic in Pener Village, Pangkah Subdistrict, Tegal Regency. Keywords: Age, Parity, Weight Gain.